Transforming Growth Factor-β and Nuclear Factor E2–related Factor 2 Regulate Antioxidant Responses in Airway Smooth Muscle Cells: Role in Asthma - Michaeloudes, Charalambos (American Thoracic Society, 2011)
Rationale: Aberrant airway smooth muscle cell (ASMC) function and overexpression of transforming growth factor (TGF)-β, which modulates ASMC proliferative and inflammatory function and induces oxidant release, are features of asthma. Nuclear factor E2-related factor 2 (Nrf2) activates antioxidant genes conferring protection against oxidative stress. Objectives: To determine the role of Nrf2 in ASMCs and its modulation by TGF-β, and compare Nrf2 activity in ASMCs from subjects with severe and nonsevere asthma and healthy subjects. Methods: ASMCs were cultured from airways of subjects without asthma, and from airway biopsies from patients with severe and nonsevere asthma. We studied Nrf2 activation on antioxidant gene expression and proliferation, the effect of TGF-β on Nrf2 transcriptional activity, and the impact of Nrf2 activation on TGF-β–mediated proliferation and IL-6 release. Nrf2–antioxidant response elements binding and Nrf2-dependent antioxidant gene expression was determined in asthmatic ASMCs. Measurements and Main Results: Activation of Nrf2 led to up-regulation of the antioxidant genes heme oxygenase (HO)-1, NAD(P)H:quinone oxidoreductase, and manganese superoxide dismutase, and a reduction in proliferation. TGF-β reduced Nrf2-mediated antioxidant gene transcription through induction of activating transcription factor-3 expression. Nrf2 activation attenuated TGF-β–mediated reduction in HO-1, ASMC proliferation, and IL-6 release. Nrf2–antioxidant response elements binding was reduced in ASMCs from patients with severe asthma compared with ASMCs from patients with nonsevere asthma and normal subjects. HO-1 expression was reduced in ASMCs from patients with both nonsevere and severe asthma compared with healthy subjects. Conclusions: Nrf2 regulates antioxidant responses and proliferation in ASMCs and is inactivated by TGF-β. Nrf2 reduction may underlie compromised antioxidant protection and aberrant ASM function in asthma.